2011
DOI: 10.3109/10428194.2011.577850
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat induced cellular stress disrupts the p38 mitogen activated protein kinase and extracellular signal regulated kinase pathways leading to apoptosis in Waldenström macroglobulinemia cells

Abstract: Histone deacetylases (HDACs) are aberrantly expressed, and inhibitors of HDACs induce apoptosis in lymphoplasmacytic cells (LPCs) in Waldenström macroglobulinemia (WM). The molecular profile by which these agents induce apoptosis in WM LPCs remains to be delineated. We examined the activity of the histone deacetylase inhibitor, vorinostat, and dissected its pro-apoptotic pathways in WM LPCs. Vorinostat induced apoptosis in WM cells through activating specific caspases at varying times. Inhibitors of apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Vorinostat, an HDAC inhibitor, is shown to induce apoptosis of WM cells via downregulation of the cytoprotective MAPK ERK1/2 and inhibitors of apoptosis (IAP) family of proteins and activation of multiple caspases, proapoptotic MAPKs, and JNK [135]. Another HDAC inhibitor, LBH589 (panobinostat) has been shown to inhibit bone marrow stromal cell-triggered or IL-6-and IGF-1-induced proliferation of a WM cell line.…”
Section: Histone Deacetylase Inhibitorsmentioning
confidence: 98%
“…Vorinostat, an HDAC inhibitor, is shown to induce apoptosis of WM cells via downregulation of the cytoprotective MAPK ERK1/2 and inhibitors of apoptosis (IAP) family of proteins and activation of multiple caspases, proapoptotic MAPKs, and JNK [135]. Another HDAC inhibitor, LBH589 (panobinostat) has been shown to inhibit bone marrow stromal cell-triggered or IL-6-and IGF-1-induced proliferation of a WM cell line.…”
Section: Histone Deacetylase Inhibitorsmentioning
confidence: 98%
“…Different studies have unraveled the interconnections between FHL2 and a number of signaling cascades, including WNT, TNF‐α, MAPK, TGF‐β, androgen receptor, AP1, CREB/CREM, E4F1, and EpCAM 38‐47 . Furthermore, WM cells have been reported to be associated with the WNT/β‐catenin pathway and the ERK/MAPK pathway 21,48 . Thus, mutated FHL2 might contribute to WNT/β‐catenin or ERK/MAPK modulation in WM cells.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46][47] Furthermore, WM cells have been reported to be associated with the WNT/β-catenin pathway and the ERK/ MAPK pathway. 21,48 Thus, mutated FHL2 might contribute to WNT/β-catenin or ERK/MAPK modulation in WM cells. Also, PPI analysis has shown that FHL2 may interact with IL-6 and HCK, which previously have been confirmed to have a significant pathogenic effect in WM.…”
Section: T E R F D C H H C N E S L F G K K Y I L R E E S P Y C V V C F E T L F a N T C E E C G K P I G C D C K D L S Y K D R H W H E A C mentioning
confidence: 99%